2017
DOI: 10.1097/md.0000000000006761
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and polypharmacy in diabetic patients with NAFLD

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 49 publications
(48 reference statements)
2
53
0
4
Order By: Relevance
“…Comorbidity is characteristic for NAFLD with frequent other chronic concomitant diseases. According to Patel et al (2017), the most common comorbidities are MS (94%), "depression" diagnosed by patients (44%), coronary heart disease (32%), obstructive sleep apnea (32%), and 59% cases of NAFLD with DM-2 are characterized by polypharmacy (Patel et al, 2017). Jonathan et al (2016) revealed that NAFLD and DM-2 association leads to a higher rate of treatment resistant DM-2 and diabetic microangiopathy development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comorbidity is characteristic for NAFLD with frequent other chronic concomitant diseases. According to Patel et al (2017), the most common comorbidities are MS (94%), "depression" diagnosed by patients (44%), coronary heart disease (32%), obstructive sleep apnea (32%), and 59% cases of NAFLD with DM-2 are characterized by polypharmacy (Patel et al, 2017). Jonathan et al (2016) revealed that NAFLD and DM-2 association leads to a higher rate of treatment resistant DM-2 and diabetic microangiopathy development.…”
Section: Discussionmentioning
confidence: 99%
“…IR can lead to NAFLD and NAFLD can cause hepatic IR, so NAFLD patients are at high risk of complete MS or its development of its components especially DM-2 (Gaggini et al, 2013;Firneisz, 2014). In addition to higher probability of death due to hepatic complications (liver failure, portal hypertension complications, hepatocellular carcinoma) (Armstrong et al, 2014), those patients are prone to higher incidence of cardiovascular diseases (Patel et al, 2017). The dangerous feature of NAFLD is an asymptomatic course especially during the initial stage (hepatosteatosis) which can be presented without lab tests showing abnormalities, which makes it difficult and sometimes even impossible to diagnose in time and start the early treatment for prevention of both hepatic and extrahepatic complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…et al, 2018). Проте дисліпідемія при НАЖХП є фактором високого кардіоваскулярного ризику (Patel P.J. et al, 2017) і, згідно з рекомендаціями Європейської асоціації з вивчення захворювань печінки (European Association for the Study of the Liver -EASL), Європейської асоціації з вивчення цукрового діабету (European Association for the Study of Diabetes -EASD) та Європейської асоціації з вивчення ожиріння (European Association for the Study of Obesity -EASO), потребує призначення гіполіпідемічної фармакотерапії, найчастіше -статинів (EASL/ EASD/EASO, 2016).…”
Section: вступunclassified
“…Тому актуальним є пошук альтернативних гіполіпідемічних ліків. Враховуючи те, що НАЖХП -захворювання з характерною коморбідністю, яке часто призводить до поліпрагмазії (Patel P.J. et al, 2017), у лікуванні доцільно віддавати перевагу препаратам із багатогранною дією (Berlanga A. et al, 2014).…”
Section: вступunclassified